Hybridity in nonprofit organizations: organizational perspectives on combining multiple logics - Malhotra, Aastha (Journal of business ethics, 2025)
Seeking to better understand how nonprofit organizations (NPOs) manage hybridity, we investigated what distinguishes NPOs that combine multiple logics in productive and unproductive ways. We collected and analyzed data from six case studies of NPOs delivering social services in Australia. Our findings reveal that organizational members of NPOs take a perspective on their hybrid nature which comprises four elements: motivational framing, actor engagement, resourcing attitude, and governance orientation. NPOs that combine multiple logics in productive and unproductive ways, respectively, are distinguished by (1) a compelling or confused motivational framing for combining logics; (2) actors having active and shared, or passive and isolated, engagement with multiple logics; (3) attitudes toward resourcing multiple logics that are either coherent or competitive; and (4) a governance orientation toward multiple logics as opportunities to leverage or problems to resist. Our findings contribute to the literature by deepening understanding of the interplay between complex constellations of multiple logics in NPOs, including religious and professional logics. We also develop a model of organizational perspectives on hybridity and their implications for distinguishing NPOs that productively harness tensions between logics.